2006
DOI: 10.1186/1742-4690-3-93
|View full text |Cite
|
Sign up to set email alerts
|

PRMT6 diminishes HIV-1 Rev binding to and export of viral RNA

Abstract: Background: The HIV-1 Rev protein mediates nuclear export of unspliced and partially spliced viral RNA through interaction with the Rev response element (RRE) by means of an arginine rich motif that is similar to the one found in Tat. Since Tat is known to be asymmetrically arginine dimethylated by protein arginine methyltransferase 6 (PRMT6) in its arginine rich motif, we investigated whether the Rev protein could act as a substrate for this enzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 63 publications
1
39
0
1
Order By: Relevance
“…ity. PRMT6 has been shown to inhibit HIV-1 transcription through the methylation of Tat, Rev, and the nucleocapsid proteins (69,70,71). PRMT1 has been shown to methylate and inhibit hepatitis C virus (HCV) NS3 protein, but in turn, HCV counteracts PRMT1 repressive activity by activating protein phosphatase 2, which inhibits PRMT1 (72,73).…”
Section: Discussionmentioning
confidence: 99%
“…ity. PRMT6 has been shown to inhibit HIV-1 transcription through the methylation of Tat, Rev, and the nucleocapsid proteins (69,70,71). PRMT1 has been shown to methylate and inhibit hepatitis C virus (HCV) NS3 protein, but in turn, HCV counteracts PRMT1 repressive activity by activating protein phosphatase 2, which inhibits PRMT1 (72,73).…”
Section: Discussionmentioning
confidence: 99%
“…An important aspect of our synthesis is the use of the one-pot approach to include the desulfurization step; this reduces the number of purification steps and significantly increases the synthesis yield. Having these synthesis tools in hand, we plan to study the effect of post-translational modifications [54][55][56] on the function and structure of the Rev protein, along with introducing chemical switches [57,58] to control Rev folding and self-assembly, to better understand these processes on the function of Rev protein. [4,53,59] …”
Section: Expression Of Hiv-1 Revmentioning
confidence: 99%
“…PRMT6 localizes exclusively to the cell nucleus, exhibits automethylation, and methylates in vitro glycine-and arginine-rich (GAR) sequences in proteins (6). Despite its overlapping substrate specificity with PRMT1, some PRMT6-specific cellular targets do not contain the GAR consensus sequence (1,24), including high mobility group proteins HMGA1a and HMGA1b (25,26), DNA polymerase ␤ (27), HIV-1 trans-activator of transcription (Tat) protein (28), HIV-1 regulator of virion (Rev) protein (29), HIV-1 nucleocapsid protein (30), and histone H3 (31)(32)(33). Methylation of polymerase ␤ by PRMT6 was shown to increase its repair activity of damaged DNA, implicating PRMT6 as a regulator of base excision repair (27).…”
mentioning
confidence: 99%
“…Most recently several groups have demonstrated that PRMT6 methylation of Arg-2 on histone H3 in vivo exists in an exclusive relationship with Lys-4 methylation, thus adding to the mounting evidence that PRMT6 is a negative regulator of cellular as well as viral transcriptional activation (31)(32)(33). PRMT6 and other PRMTs are now a focus of attention for the development of inhibitors targeting methyl transfer activity (20,29,30,(35)(36)(37).…”
mentioning
confidence: 99%